Agricultural and Forest Residues towards Renewable Chemicals and Materials Using Microwave Liquefaction. (9th October 2019) - Shao, Huijuan; Zhao, Hongli; Xie, Jiulong; Qi, Jinqiu; Shupe, Todd F.
Abstract : Microwave-assisted liquefaction is regarded as a promising thermochemical approach to produce renewable and sustainable chemicals and materials from lignocellulosic biomass. Agricultural and forest residues as sources of lignocellulosic biomass have great potential in this regard. With process optimizations, several biomass types have been subjected to liquefaction in different solvents with various catalysts. The products from recent microwave liquefaction with and without further fractionation have been thoroughly analyzed and used for the synthesis of biomaterials. Renewable chemicals, polyurethane foams with partial use of renewable raw materials, and phenolic resins have been the main products from microwave-liquefied products. Further research on microwave liquefaction mechanisms and scalable production should be enhanced to fully evaluate the economic and environmental benefits. This work presents an overview on achievements using liquefaction in combination with microwave energy to convert lignocellulosic biomass into value-added products and chemicals.